2021
DOI: 10.1186/s12859-021-03990-3
|View full text |Cite
|
Sign up to set email alerts
|

Statistical image processing quantifies the changes in cytoplasmic texture associated with aging in Caenorhabditis elegans oocytes

Abstract: Background Oocyte quality decreases with aging, thereby increasing errors in fertilization, chromosome segregation, and embryonic cleavage. Oocyte appearance also changes with aging, suggesting a functional relationship between oocyte quality and appearance. However, no methods are available to objectively quantify age-associated changes in oocyte appearance. Results We show that statistical image processing of Nomarski differential interference co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…It is possible that in some cell populations, structural changes associated with aging and senescence may reflect on some GLCM features. This was indicated in previous research in the nematode Caenorhabditis elegans where the authors showed that some GLCM features such as COR may be used in the quantification of structural hallmarks of oocyte aging (Imakubo et al, 2021). Another possible medical application of GLCM is for the detection of pathologically changed cells and nuclei during cancer development.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…It is possible that in some cell populations, structural changes associated with aging and senescence may reflect on some GLCM features. This was indicated in previous research in the nematode Caenorhabditis elegans where the authors showed that some GLCM features such as COR may be used in the quantification of structural hallmarks of oocyte aging (Imakubo et al, 2021). Another possible medical application of GLCM is for the detection of pathologically changed cells and nuclei during cancer development.…”
Section: Discussionmentioning
confidence: 78%
“…Previously, it has been successfully applied in medicine for the evaluation of radiological images such as the ones obtained from computerized tomography and nuclear magnetic resonance (Cao et al, 2019; Feng & Ding, 2020). In pathology, histology, and cell biology, GLCM features can be potentially sensitive indicators of various subtle structural alterations occurring during cellular senescence and cell damage (Pantic et al, 2016; Imakubo et al, 2021). Features such as angular second moment (ASM; an indirect measure of textural uniformity) and inverse difference moment (an indirect indicator of textural homogeneity) can be used to identify and quantify changes in nuclear chromatin patterns that take place after cell exposure to various potentially toxic substances.…”
Section: Introductionmentioning
confidence: 99%
“…By about day 5 of adulthood, oocytes show overt signs of deterioration (Garigan et al, 2002;Luo et al, 2010). They become morphologically disordered, and the progeny they give rise to show a higher incidence of chromosome non-disjunction and embryonic lethality, even if the old hermaphrodite is provided with sperm from a young male (Killian and Hubbard, 2001;Luo et al, 2010;Templeman et al, 2018;Imakubo et al, 2021). Though never fully avoided, defects in late life reproductive quality are delayed in long-lived mutants.…”
Section: How Is Stem Cell Fate and Function Altered With Age?mentioning
confidence: 99%
“…Many studies on large-scale, data-based gene function analysis have been carried out and achieved fruitful results [1][2][3][4]. Among them, research based on differential interference contrast (DIC) imaging and RNA interference (RNAi) techniques have become prevalent and have gained extensive applications [5,6]. In [7], Narayanaswamy R. et al developed spotted cell microarrays for measuring cellular phenotypes on a large scale to identify genes involved in the response of yeast to mating pheromones.…”
Section: Introductionmentioning
confidence: 99%